2017
DOI: 10.3892/ijmm.2017.3285
|View full text |Cite
|
Sign up to set email alerts
|

Different roles of Akt and mechanistic target of rapamycin in serum‑dependent chondroprotection of human osteoarthritic chondrocytes

Abstract: Despite various animal serums being used widely to culture chondrocytes, the regulatory mechanism of serum on chondrocyte activities has not been elucidated. In the present study, human osteoarthritis (OA) chondrocytes were used to perform in vitro investigations on the effect of different concentrations of bovine fetal serum on extracellular matrix synthesis, cell proliferation and autophagy using the Cell Counting Kit‑8 analysis, a laser‑scanning confocal microscope, and western blot analysis. The results de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Adiponectin protects chondrocytes from apoptosis related to oxidative stress by inducing autophagy possibly via PI3K/Akt/mTOR (Hu et al, 2017 ). Other biological products such as Platelet rich plasma (PRP), adipose-stem cells, and serum have also shown efficacy at protecting from degeneration and inflammation through autophagy-related mechanisms in cartilage disease (Jiang et al, 2016 ; Moussa et al, 2017 ; Zhang et al, 2018 ).…”
Section: Current Development In Innovative Therapeutic Approachesmentioning
confidence: 99%
“…Adiponectin protects chondrocytes from apoptosis related to oxidative stress by inducing autophagy possibly via PI3K/Akt/mTOR (Hu et al, 2017 ). Other biological products such as Platelet rich plasma (PRP), adipose-stem cells, and serum have also shown efficacy at protecting from degeneration and inflammation through autophagy-related mechanisms in cartilage disease (Jiang et al, 2016 ; Moussa et al, 2017 ; Zhang et al, 2018 ).…”
Section: Current Development In Innovative Therapeutic Approachesmentioning
confidence: 99%
“…Beclin-1 overexpression mitigated the phsophoinositol-3 kinase (PI3K)/protein kinase B (AKT)/mTOR signaling pathway, which led to increased cell viability, and inhibition of apoptosis and MMP expression ( 38 ). Furthermore, inhibition of mTOR by treatment with rapamycin led to significant suppression of cartilage degeneration in a surgically induced OA mouse model and chondroprotection in human OA chondrocytes ( 39 , 40 ). In our experiments, 29-kDa FN-f down-regulated LC3-II level by activating the mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The suppression of mTORC1 promotes autophagy, maintains cell proliferation, and reduces the expression of inflammatory factors expression in osteoarthritis [49]. Moreover, a previous experimental study showed that an intra-articularly injected mTORC1 inhibitor rapamycin could activate chondrocyte autophagy and delay cartilage degradation in an animal model [26].…”
Section: P R E P R I N Tmentioning
confidence: 97%